ANALISA PREDIKSI KEBANGKRUTAN METODE ALTMAN Z”SCORE PADA PT HANSON INTERNATIONAL, Tbk - Safri Safri (JURNAL MITRA MANAJEMEN, 2012)
AbstactThe purpose of this study was to predict bankruptcy PT Hanson International, Inc., using the methodof Altman Z (Zeta) - Score. Data collection techniques to the calculation are taken from the company'sfinancial statements for 5 (five) years, the financial statements in the form of balance sheets and incomestatement. The method used is the method of Altman Z “'Score, because the object of research is a publiccompany. And corporate accounting period is the accounting period 2006 to 2010.Decision making based on the calculation of the equation Altman Z